Thinking and understanding of six major problems in the large-scale development of 5GtoB - Shiliang HU (Dianxin kexue)
In order to better promote the high-quality development of 5GtoB, an in-depth analysis of the six major issues of 5GtoB large-scale development is carried out: the driving force of 5GtoB development, what stage of 5GtoB development, the essence of 5GtoB development, whether 5GtoB can become the second curve of operators, how to innovate 5GtoB business models, and the management support of 5GtoB development.The analysis results show that at present, China's 5GtoB is showing a booming trend and is expected to become the ＆quot;second curve＆quot; of operators.However, at present, the development of 5GtoB in China is still in the development stage of relying on policy-driven as the main driving force, and it is still in the stage of creating industry benchmarking application cases.The essence of 5G development is to do a good job in products and solutions, promote business model innovation, and establish an efficient management model.